COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN UNIT USAHA GULA SEMUT (Studi Kasus Pada Bumdes Kabul Ciptaku Desa Langgongsari Kecamatan Cilongok Kabupaten Banyumas) - Dimas Agus Setiawan; Chamid Sutikno; Indah Ayu Permana Pribadi; Ariesta Amanda; Zaula Rizqi Atika (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study is motivated by the practice of collaborative governance in the management of the palm sugar business unit within a Village-Owned Enterprise (BUMDes), which requires further examination to understand the dynamics of inter-actor collaboration in export-oriented village enterprises. This research aims to analyze the implementation of collaborative governance in the management of the palm sugar business unit at BUMDes Kabul Ciptaku, Langgongsari Village, which has successfully penetrated international markets. The novelty of this study lies in its focus on collaborative patterns among stakeholders in managing an export-based BUMDes at the village level. This study employed a descriptive qualitative method with data collected through interviews, observations, and documentation. Informants were selected purposively, consisting of village government officials, BUMDes managers, farmers, and the private partner CV Javari. Data validity was ensured through source and technique triangulation. Data analysis referred to the collaborative governance model proposed by Ansell and Gash. The findings reveal that collaboration emerged due to disparities in resources and capacities among actors, leading each party to perform complementary roles. The collaborative process was carried out through direct communication, trust-building, and sustained commitment among stakeholders, although farmers’ involvement in strategic decision-making remained limited due to the dominance of technical coordination. This collaboration succeeded in expanding export market access and increasing the economic value of palm sugar products; however, institutional strengthening and broader actor participation are still needed to support the sustainability of BUMDes.